Abnormal expression of SLIT3 induces intravillous vascularization dysplasia in ectopic pregnancy - Zhu,Qian; Zhao,Xiaoya; Zhang,Duo; Xia,Wei; Zhang,Jian (PeerJ, 2023)
Objective To investigate whether the morphology, capillary number, and transcriptome expression profiles of ectopic pregnancy (EP) villi differ from those of normal pregnancy (NP) villi. Methods Hematoxylin-eosin (HE) and immunohistochemistry (IHC) staining for CD31 were conducted to compare differences in morphology and capillary number between EP and NP villi. Differentially expressed (DE) miRNAs and mRNAs were determined from transcriptome sequencing of both types of villi and used to construct a miRNA–mRNA network, from which hub genes were identified. Candidate DE-miRNAs and DE-mRNAs were validated by quantitative reverse transcription (qRT)-PCR. Correlations were identified between the number of capillaries and serum beta human chorionic gonadotropin (β-HCG) levels and between the expression levels of hub genes associated with angiogenesis and β-HCG levels. Results The mean and total cross-sectional areas of placental villi were significantly increased in EP compared with NP villi. Capillary density was greatly reduced in EP villi and was positively correlated with β-HCG levels. A total of 49 DE-miRNAs and 625 DE-mRNAs were identified from the sequencing data. An integrated analysis established a miRNA–mRNA network containing 32 DE-miRNAs and 103 DE-mRNAs. Based on the validation of hub mRNAs and miRNAs in the network, a regulatory pathway involving miR-491-5p–SLIT3 was discovered, which may have a role in the development of villous capillaries. Conclusion Villus morphology, capillary number, and miRNA/mRNA expression profiles in villous tissues were aberrant in EP placentas. Specifically, SLIT3, which is regulated by miR-491-5p, may contribute to the regulation of villous angiogenesis and was established as a putative predictor of chorionic villus development, providing a basis for future research.
Keywords: Ectopic pregnancy; Villus capillary; miRNA–mRNA network; Bioinformatics analysis